Pilihan Hukum dan Yurisdiksi Dalam Kontrak Digital Antarnegara - Ayu Herlin Norma Yunita; Andin Martiasari (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2026)
Advances in information and communication technology have accelerated the use of digital contracts in cross-border commercial transactions, raising legal challenges regarding choice of law and jurisdiction. This study examines the nature of choice of law and jurisdiction in cross-border digital contracts within the Indonesian legal system using a normative legal methodology with a statutory and conceptual approach. The findings indicate that Indonesian law has recognized the principle of party autonomy in international electronic contracts through Article 18 of the ITE Law; however, its effectiveness is limited by mandatory legal norms and public policy. Therefore, clear and balanced contractual clauses are necessary to ensure substantive legal certainty in cross-border digital transactions.